High-Protein Concentrated Pro-Yogurt (Pro-WPI) Enriched With Whey Protein Isolate Improved Athletic Anemia and Performance in a Placebo-Controlled Study - Gomaa, Mohamed A. E.; Allam, Marwa G.; Haridi, Abdallah A. I. M.; Eliwa, Alaa-Eldin M.; Darwish, Amira M. G. (Frontiers in Nutrition, 2022)
Upcoming developments are attracting attention to both high-protein and probiotics supplementation for the sports community to promote good health and exercise performance. This study aimed at the production of high-protein concentrated pro-yogurt (Pro-WPI) enriched with 10 and 20% whey protein isolate (WPI) and investigation of the response of daily consumption on anthropometric, hematology parameters, and athletic performance in parallel with safety consideration assessment. Twenty-four athletes (19.6 ± 1.45 years; 175.96 ± 5.24 cm; 73.16 ± 8.65 kg) were participated in a randomized placebo-control study. They consumed Pro-WPI products with 10 (T1) and 20% (T2) WPI for treatments G1 (Pro-WPI30) and G2 (Pro-WPI60), respectively, 3 times per day/5 days per week/9 weeks. The taste of Pro-WPI products was sour and cheesy, while mouthfeel was described as soft and thick because of the increased protein content in T1 and T2 (14.15 and 22.58%). The hemoglobin of the athletes increased significantly from a baseline of 12.69 g/dl to 16 and 16.66 g/dl in G1 and G2, respectively. Furthermore, the athletic performance was enhanced in vertical jump, long jump, sprinting velocity, half squats, and pushups, which reached 58.75 cm, 255 cm, 3.5 m/s, 218.75 counts, and 85 counts, respectively in G2. The healthy gut microbiome (probiotics) in parallel with increased iron bioavailability by mineral binding (whey bioactive peptides), influenced iron status and can represent a healthy practice to improve athletic anemia and performance. On the other hand, urinary albumin exceeded the border of reference range (<30 mg/g) and reached 38.25 and 44.13 mg/g in G1 and G2, while urine pH was in the normal range (4.5–8). Increased urinary albumin might be due to high rates of protein metabolism that follow high protein intake. This study provided preliminary information on metabolic responses to high protein concentrated yogurt intake in athletes who engaged in daily exercise. Further studies are needed to determine the recommended intensity of 10 and 20% Pro-WPI product consumption to achieve its benefits and avoid implications on kidney function.